KEBIJAKAN HUKUM PERTAMBANGAN YANG BERKEADILAN BAGI INVESTOR ATAS PENCABUTAN IZIN SEPIHAK OLEH PEMERINTAH PASCA BERLAKUNYA UU NO 3 TAHUN 2020 - Velinka Permatasari (Veteran Law Review, 2023)
This research will emphasize the discussion of the Government must be fair in its attitude and provide convenience for all legal subjects, including investors who are trying to obtain their rights in running a business. However, this is not reflected in the attitude of the Government or BKPM which revokes mining licenses to business actors without any clarity. As in Decision Number 215/G/2022/PTUN.JKT. The research method used is normative legal research. The results showed that IUP revocation is the last resort for companies that have been manifestly unable to fulfill their legal obligations, after being given warning sanctions and termination of exploration activities / production operations either partially or completely. As for the procedure for revocation of IUP, IUP cannot be immediately revoked without going through the procedure of written warning and temporary suspension first, which is also regulated in Article 188 of PP 96 of 2021. In the case of the State Administrative Court Decision No. 215/G/2022/PTUN.JKT, it is known that BKPM issued a Decree of Revocation of Permit of the Government of the Republic of Indonesia Number 20220218-01- 35400 regarding the Revocation of Mining Business License to PT Megatop Inti Selaras without a warning letter for 3 (three) times as regulated in Article 186. The actions taken by the BKPM are not in line with Article 183 of Government Regulation No. 96 of 2021.